Antacid Use and Reduced Bioavailability of Oral Drugs - Srinivas, Nuggehally R (Arzneimittelforschung, 2009)
A close scrutiny of deployment of the present day home medicines has shown increased indulgence of antacids as a household remedy. While such household interventions are considered innocuous, it could trigger potential drug-drug inter-action(s), if the subject is taking other prescription medicine(s). Examination of the literature indicated that co-administration of antacids may have the potential to cause therapy failures due to reduced oral bioavailability of several drugs. Additionally, fortified foods and beverages with mineral supplement may also have the potential to reduce the bioavailability of oral drugs.On the basis of this review a number of drugs displayed reduced oral bioavailability in the presence of antacids. However, almost one third of the reviewed drugs showed a drastic bioavailability reduction (< 50%) warranting total avoidance of antacid ingestion in such drug uses. If antacid use is warranted, it needs to be carefully monitored in relation to the administration of the drug (either pre or post drug administration). It appeared that a safe window for antacid administration could be established especially for drugs that display moderate reduction of oral bioavailability. While possible mechanisms explaining the purported antacid-drug interaction are covered, additional perspectives with regard to assessment protocols for antacid-drug interaction are discussed.
Keywords: Antacids; Drug-drug interaction, oral bioavailability, pharmacokinetics